PENDAMPINGAN DAN PELATIHAN KEWIRAUSAHAAN KEPADA MASYARAKAT ASLI PAPUA KAMPUNG KUMBE GUNA MENINGKATKAN MOTIVASI BERWIRAUSAHA - Irfan Wildzan Muafa; Dewi Putri Anjar Wulan (Musamus University, 2020)
Merauke Regency has a very wide water area, with abundant sea catches. Especially in the area of ​​Kampung Kumbe which is directly adjacent to the river or Kali Kumbe, making the livelihood of most of its residents are fish seekers or fishermen. The usual catches obtained by fishermen such as moon fish, tilapia fish, shrimp, and also rebon. Most catches will be directly sold to consumers without further processing. Potential fish can be processed into fish crackers that can absorb and also open up new jobs. The problem is the lack of community understanding of entrepreneurship and also the way fish are processed into fish crackers. So that the catch is not further processed. Field surveys, training and evaluation are also conducted to support the success of community service activities. Through providing insight into entrepreneurship and training on making fish crackers by the community service team, the community will be able to make their own processed fish products. So, with the presence of businesses or processed products of the community, the economy of the Kumbe community will gradually increase. Service activities went well starting from the provision of entrepreneurial material to the training process of making fish crackers